ANALYSIS OF THE ROLE OF THE PLANNING DIVISION IN PREPARING BASIC EDUCATION BUDGETS AT THE EDUCATION OFFICE OF MESUJI REGENCY - Sinta Oktavia Pratiwi; M. Oktavianur (International Journal of Multidisciplinary Reseach, 2026)
This study used a descriptive qualitative research method. The method was applied to describe and qualitatively examine the role of the Planning Division in preparing basic education budgets at the Education Office of Mesuji Regency. All data were obtained directly from field informants through interviews and document studies. The findings show that: (1) in the dimension of goal and priority setting, budget preparation has been directed to align with basic education needs, regional development priorities, and education service targets; (2) in the dimension of program and budget synchronization, there is alignment among programs, activities, indicators, targets, and budget allocations so that each basic education program has realistic and appropriate budget support; (3) in the dimension of performance indicator preparation, every program and activity has clear, measurable, and relevant indicators; (4) in the dimension of efficiency and resource allocation, budget use has been directed to be more targeted, economical, and priority-based; and (5) in the dimension of control and evaluation, the suitability between plans, implementation, budget realization, and performance achievements has been monitored. Inhibiting aspects include limited data, limited budget, weak interdivisional coordination, performance indicators that are not yet outcome-based, resource allocation that is not fully targeted, and evaluation that remains administrative.